Is bilingualism really an advantage? What about individuals with autism? - Ahmet Aslan; Tayfun Kara (Acta Medica Alanya)
The prevalence of autism spectrum disorder (ASD) is rising globally, making the identification of at-risk groups increasingly important. The proportion of bilingual families has also increased in recent years. There are very few studies examining the relationship between ASD and bilingualism. Although bilingualism is considered an advantage in terms of child development, its consequences in the presence of ASD are unclear. Therefore, there is no consensus among professionals in this field on the subject of bilingualism. Being bilingual is a factor that should not be overlooked during interventions for children with ASD. More research is needed to examine the relationship between being bilingual and ASD longitudinally.